2020
DOI: 10.1002/chem.201905358
|View full text |Cite
|
Sign up to set email alerts
|

Sulfuryl Fluoride Mediated Synthesis of Amides and Amidines from Ketoximes via Beckmann Rearrangement

Abstract: A metal‐free and redox‐neutral method for Beckmann rearrangement employing inexpensive and readily available SO2F2 gas is described. The reported transformation proceeds at ambient temperature and is compatible with a wide range of sterically and electronically diverse aromatic, heteroaromatic, aliphatic and lignin‐like oximes providing amides in good to excellent yields. The reaction proceeds through the formation of an imidoyl fluoride intermediate that can also be used for the synthesis of amidines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…2 Recently, Fokin et al showed that the cation 2 could be trapped by sulfuryl fluoride (SO 2 F 2 ) to afford fluorinated intermediates, that is, imidoyl fluorides 4, from oximes 1 (see Scheme 1b). 3 However, these intermediates 4 have not been isolated. Further, sulfuryl fluoride is not a desirable reagent, because it is toxic and a potential greenhouse gas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Recently, Fokin et al showed that the cation 2 could be trapped by sulfuryl fluoride (SO 2 F 2 ) to afford fluorinated intermediates, that is, imidoyl fluorides 4, from oximes 1 (see Scheme 1b). 3 However, these intermediates 4 have not been isolated. Further, sulfuryl fluoride is not a desirable reagent, because it is toxic and a potential greenhouse gas.…”
mentioning
confidence: 99%
“…The Beckmann rearrangement of oximes 1 in acids to provide amides 3 is well-known (Scheme a), but the intermediate N -ethylidyne-ammonium cation 2 has received little attention . Recently, Fokin et al showed that the cation 2 could be trapped by sulfuryl fluoride (SO 2 F 2 ) to afford fluorinated intermediates, that is, imidoyl fluorides 4 , from oximes 1 (see Scheme b) . However, these intermediates 4 have not been isolated.…”
mentioning
confidence: 99%
“…21 Recently, Ding, Qin and Fokin groups reported rapid and mild SO 2 F 2 -promoted dehydration of oxime. 22 However, the use of a greenhouse gas SO 2 F 2 is not safe as it may leak out in operation. 23 Although the organoselenium-catalyzed dehydration of aldoximes can produce nitriles under environment friendly conditions, it required for hours up to days.…”
mentioning
confidence: 99%
“…Meanwhile, a dramatic upfield shift in 19 F NMR from −20.45 ppm to −150.70 ppm also suggests the cleavage of the C α −F bond on intermediate Int-F ( Figures 5 A, III, and S106 ). In addition, intermediate Int-F could be captured by N -methylbenzylamine to afford the corresponding amidine 14 ( Gurjar and Fokin, 2020 ) in 60% NMR yield ( Figures 5 E, S107 , and S108 ). This result further supports the formation of intermediate Int-F .…”
Section: Discussionmentioning
confidence: 99%